Concentration attention and its relationship to the decision-making of referees in the Egyptian soccer federation - Hussen Refaei, M.; Adel, I.O.; Mohammed Refaei, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The soccer match is run by the referee and assistants to achieve fair-play between the two teams in line with the rules of soccer. Concentration attention plays an important role in influencing the efficiency of the referees performance where the lack of concentration attention may lead to altered performance. The results of several studies have shown a relationship between ability to concentrate and the motor performances of athletes and decision-making is an important factor for success in sport As such, referees must respond quickly when making decisions during the game despite the external influences that may cause pressure on the referee and his assistants . External pressures on athletes may lead to the inability to produce focused concentration and attention and effective decision-making and under precarious conditions that often prevail in sports. It has been shown that many problems are observed as a function of the many problems that may occur due to incorrect decisions made by the referee. This study aimed to identify the concentration attention capability of soccer referees and the relationship between this capability and decision making.